2001
DOI: 10.1117/12.435896
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic interferometric method for investigation of deformations of building structure

Abstract: It is shown, that the singlefiber doublemode interferometer implanted into structure of a tested concrete unit allows to measure the unit structural deflection, absolute elongation and residual deformations in real time with accuracy not worse, than 0,05 im . It is also shown, that the developed interferometric method allows to indicate a point of time of unit's crack initiation and to estimate the crack opening displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At present, numerous different types of fiber optic sensors have been developed. For example, the authors [2] suggested the design of a single fiber double mode interferometer to control deformation of concrete constructions, in particular buildings. In the study [3], the possibility of registration and spatial reconstruction of acoustic field created in a solid plate by an adaptive 32-channel hologram interferometer was examined.…”
Section: Introductionmentioning
confidence: 99%
“…At present, numerous different types of fiber optic sensors have been developed. For example, the authors [2] suggested the design of a single fiber double mode interferometer to control deformation of concrete constructions, in particular buildings. In the study [3], the possibility of registration and spatial reconstruction of acoustic field created in a solid plate by an adaptive 32-channel hologram interferometer was examined.…”
Section: Introductionmentioning
confidence: 99%